2016
DOI: 10.3390/cancers8060057
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling in Renal Cell Carcinoma

Abstract: Renal cell carcinoma (RCC) accounts for 90% of all kidney cancers. Due to poor diagnosis, high resistance to the systemic therapies and the fact that most RCC cases occur sporadically, current research switched its focus on studying the molecular mechanisms underlying RCC. The aim is the discovery of new effective and less toxic anti-cancer drugs and novel diagnostic markers. Besides the PI3K/Akt/mTOR, HGF/Met and VHL/hypoxia cellular signaling pathways, the involvement of the Wnt/β-catenin pathway in RCC is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
80
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 105 publications
0
80
0
Order By: Relevance
“…Recent studies have also shown aberrant signal transduction of WNT/β-catenin is correlated with an aggressive phenotype [15, 28, 29]. However, the exact mechanisem of WNT/β-catenin classical pathway involved in RCC progression is still under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also shown aberrant signal transduction of WNT/β-catenin is correlated with an aggressive phenotype [15, 28, 29]. However, the exact mechanisem of WNT/β-catenin classical pathway involved in RCC progression is still under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the binding partner of DKK-3 on the cell surface remains to be elucidated, these findings assist in clarifying the anti-cancer mechanisms of extracellular DKK-3. The Wnt signaling pathway serves an important role in the carcinogenesis and the progression of renal cell carcinoma (23), and the in vivo tumor-suppressive effects of the recombinant full length DKK-3 protein were previously demonstrated in the RENCa tumor model of murine renal carcinoma (24). Therefore, recombinant DKK-3 protein may be a promising agent for treating renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney cancer accounts for approximately 2–3% of all cancers worldwide each year, and renal cell carcinoma (RCC) is thought to be the most common type of kidney malignancy with a slight male predominance . The incidence of RCC has increased in most regions during recent decades, and the morbidity of this disease is consistently increasing annually . Nearly half of patients die within the first 5 years after diagnosis with this disease .…”
Section: Introductionmentioning
confidence: 99%